Saponins from Aesculus wilsonii seeds exert anti-inflammatory activity through the suppression of NF-κB and NLRP3 pathway - Huimin Li; Huina Cao; Jingya Ruan; Yuzheng Wu; Dingshan Yang; Qian Gao; Dan Wang; Qian Chen; Yi Zhang; Tao Wang (Arabian Journal of Chemistry, 2023)
The seeds of Aesculus wilsonii were reported to be rich in saponins and have anti-inflammatory activity. However, the phytochemistry investigation of its saponins is not clear yet, and the bioactivity is also rare. Therefore, the detailed constituents' study on saponins from A. wilsonii seeds was performed, and eleven new isolates, aeswilsaponins IA–IH (1–8), ⅡA (9), ⅡB (10) and ⅢC (11), along with twenty reported analogs (12–31) were yielded. All of them were examined for their inhibitory effects on NO release in LPS-induced RAW264.7 cells, indicating that 1, 4, 5, 12, 18, 22–24, 26, and 27 had potential anti-inflammatory activity. Moreover, NF-κB activity and the expression of NF-κB-linked genes were all examined on LPS-stimulated RAW 264.7 cells. The results suggested the anti-inflammation mechanism was at least partially related to the inhibition of NF-κB activity and consequent inhibition of p-IKK-α/β/IKK-α/β, iNOS, COX-2, IL-6, and TNF-α by compounds 4 and 5, as well as the inhibition of p-IKK-α/β/IKK-α/β, COX-2, and TNF-α by compound 1. Furtherly, in the LPS/ATP-induced peritoneal macrophages (PMs) cell model, the three tested ones had the inhibitory tendency on the NLRP3 inflammasome priming and assembling genes, NLRP3, pro-IL-1β, ASC, cleaved IL-1β, and cleaved caspase-1. Among them, compounds 4 and 5 inhibited the expression level of p-IKK-α/β/IKKα/β and p-p65/p65, and 1 reduced the expression level of p-p65/p65, clarifying that they may inhibit inflammatory response through NF-κB/NLRP3 signaling pathway. This work will provide a potential molecular mechanism of ''Suo Luo Zi'' and its saponins and supply novel candidates for treating inflammation-related diseases.